2015
DOI: 10.2460/ajvr.76.10.869
|View full text |Cite
|
Sign up to set email alerts
|

Development of a model to induce transient synovitis and lameness in the hip joint of dogs

Abstract: Results indicated that injection of a sodium urate suspension into the hip joint of healthy dogs reliably induced synovitis and signs of pain and lameness in the ipsilateral pelvic limb that lasted 24 hours. This model can be used in conjunction with instrumented gait analysis to provide information on gait changes associated with hip joint disease and might be useful for evaluating the efficacy of analgesics or other interventions for the treatment of hip joint disease in dogs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
(33 reference statements)
0
2
0
Order By: Relevance
“…In humans, most pain occurs within 24 h, and symptoms resolve within 14 days even without treatment ( 16 , 17 ). Similarly, Hassan et al reported the symptoms to be most severe at 4 h and relieved after 24 h in the dogs when a sodium urate suspension is injected intra-articularly ( 18 ). The owners of the animals in this case report also described the symptoms as intermittent or shifting lameness, similar to the time course of symptomatic episodes that can be seen in humans.…”
Section: Discussionmentioning
confidence: 97%
“…In humans, most pain occurs within 24 h, and symptoms resolve within 14 days even without treatment ( 16 , 17 ). Similarly, Hassan et al reported the symptoms to be most severe at 4 h and relieved after 24 h in the dogs when a sodium urate suspension is injected intra-articularly ( 18 ). The owners of the animals in this case report also described the symptoms as intermittent or shifting lameness, similar to the time course of symptomatic episodes that can be seen in humans.…”
Section: Discussionmentioning
confidence: 97%
“…Ideally, a valuable animal model for this inflammatory-related disease should be suitable for the evaluation of immune biomarkers and kinematic parameters. At the present, several animal models of synovitis have been described including dogs [15], rats [16] and rabbits [17]. However, due to their translational applicability, other large animal models such as pigs or sheep have been considered as the more appropriate models for this kind of studies [18].…”
Section: Introductionmentioning
confidence: 99%